Academic burnout in psychology and health-allied sciences: the BENDiT-EU program for students and staff in higher education - Kourea, Lefki; Papanastasiou, Elena C.; Diaconescu, Liliana Veronica; Popa-Velea, Ovidiu (Frontiers in Psychology, 2023)
Studying at university involves demanding academic and clinical training requirements for students from Psychology and other health-allied fields, potentially having severe physical and mental health implications. Existing training programs for addressing burnout have focused thus far on specific areas (e.g., stress management, physical exercise, mindfulness meditation, etc.) with promising outcomes. However, no comprehensive programs have been developed to train students and staff in the early identification of burnout signs and characteristics as well as in self-assessing personal needs and habits (i.e., primary prevention), or in identifying community resources and evidence-based strategies to overcome burnout (i.e., secondary prevention). This paper describes the content development, refinement, and piloting process of the BENDiT-EU program as part of a European collaborative to address academic burnout for health-allied students. Piloting results showed that participants viewed the program positively and provided helpful suggestions for content improvement and training delivery. Future research directions should target experimental investigations of the program's effectiveness and the longitudinal interaction of burnout with other variables (e.g., resilience).